METHODOLOGICAL APPROACH TO THE FORMATION OF STRATEGIC PROGRAMS OF DEVELOPMENT OF MINERAL DEPOSITS OF LOCAL IMPORTANCE - lexey Cherepovitsyn; Galina Peshkova (Вестник Северо-Кавказского федерального университета)
It defines three groups of parameters that must be considered in the development of strategic programs of development ofmineral resources complex of local importance. It identifies five successive stages in the strategic programming of the regional mining industry. The structure of the model-methodical complex of the formation of the strategic program of MRC regional significance is developed.